Hyperactive piggyBac transposase improves transformation efficiency in diverse insect species. - Eckermann, K.N.; Ahmed, H.M.M.; KaramiNejadRanjbar, M.; Dippel, S.; Ogaugwu, C.E.; Kitzmann, P.; Isah, M.D.; Wimmer, E.A. (Insect Biochemistry and Molecular Biology, 2018)
Even in times of advanced site-specific genome editing tools, the improvement of DNA transposases is still on high demand in the field of transgenesis: especially in emerging model systems where evaluated integrase landing sites have not yet been created and more importantly in non-model organisms such as agricultural pests and disease vectors, in which reliable sequence information and genome annotations are still pending. In fact, random insertional mutagenesis is essential to identify new genomic locations that are not influenced by position effects and thus can serve as future stable transgene integration sites. In this respect, a hyperactive version of the most widely used piggyBac transposase (PBase) has been engineered. The hyperactive version (hyPBase) is currently available with the original insect codon-based coding sequence (ihyPBase) as well as in a mammalian codon-optimized (mhyPBase) version. Both facilitate significantly higher rates of transposition when expressed in mammalian in vitro and in vivo systems compared to the classical PBase at similar protein levels. Here we demonstrate that the usage of helper plasmids encoding the hyPBase - irrespective of the codon-usage - also strikingly increases the rate of successful germline transformation in the Mediterranean fruit fly (Medfly) Ceratitis capitata, the red flour beetle Tribolium castaneum, and the vinegar fly Drosophila melanogaster. hyPBase-encoding helpers are therefore highly suitable for the generation of transgenic strains of diverse insect orders. Depending on the species, we achieved up to 15-fold higher germline transformation rates compared to PBase and generated hard to obtain transgenic T. castaneum strains that express constructs affecting fitness and viability. Moreover, previously reported high sterility rates supposedly caused by hyPBase (iPB7), encoded by ihyPBase, could not be confirmed by our study. Therefore, we value hyPBase as an effective genetic engineering tool that we highly recommend for insect transgenesis.